Subjective experiences about virtual classes in Peruvian university students in times of COVID 19 - Sulca Chumbiauca , Kiara (2022)
The present research is of a qualitative nature that aims to know the perception of the experience of receiving virtual classes in Peruvian university students, semi-structured interviews were carried out with a group of university students, whose ages range between 18 to 40 years old. of diverse economic and cultural levels.